Enhancing Critical Reading through Technology Integration: Exploring the Effectiveness of Digital Tools in EFL Classrooms - Maspufah; Afriyeni, Yeni; Zuriati, Diana (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
EFL learners encounter many challenges in developing their reading abilities such as vocabulary gaps, grammatical difficulties, and cultural understanding. However, conventional instructional methodologies have demonstrated limitations to meet learning needs. This condition creating a compelling imperative for innovative technological solutions which personalize and optimize the reading comprehension learning experience. This research was intended to identify whether and to what extent Kahoot games as technology integration enhance learners ability in critical reading. The research implemented action research method.  The research was conducted in one cycle which consisted of five meetings, started with pre-test, treatment, and post-test. The sample was taken by adopting purposive sample. Nine students from 2023/2024 academic year from a private public college in Pekanbaru were taken as the sample. The data were collected quantitatively by utilizing quiz feature in kahoot platform, and qualitatively by using interview. The data were analyzed by using three data analysis theory. After analyzing the data, it was found that the implementation of Kahoot as one of technology integration was able to motivate learners to enhance their ability in learning various text and make learners more enjoy in learning critical reading. However, the utilize of Kahoot was not advisable for test as it had limited time to think and synthesize information from the text. It can be concluded that the implementation of technology integration through Kahoot provided positive result in learners’ critical reading.